2021
DOI: 10.1115/1.4051216
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Motion Characteristics of a Controllable Ventilated Supercavitating Vehicle Under Accelerations

Abstract: The development of a maneuverable underwater high-speed vehicle is worthy of attention and study using supercavitation drag reduction theory and technology. The supercavity shape determines the hydrodynamics of the vehicle, and especially during a maneuver, its unsteady characteristics have a significant impact on the motion stability of the vehicle. The three-dimensional dynamic model of a ventilated supercavitating vehicle is established using the unsteady supercavity dynamic model based on the rigid body dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Supercavity deforms under gravity and the cavitator's lateral force. Based on the conservation of momentum theorem, the supercavity longitudinal axis shifts caused by these two factors are formulated in Equation ( 3), where the variables and parameters are explained in our work [8].…”
Section: Supercavity Dynamic Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…Supercavity deforms under gravity and the cavitator's lateral force. Based on the conservation of momentum theorem, the supercavity longitudinal axis shifts caused by these two factors are formulated in Equation ( 3), where the variables and parameters are explained in our work [8].…”
Section: Supercavity Dynamic Modelingmentioning
confidence: 99%
“…Due to the changes in the motion parameters of the SCAV, the supercavitating flow is unsteady. Therefore, the internal gas mass conservation is considered in the following [8].…”
Section: Supercavity Dynamic Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many years ago, researchers carried out a series of scientific investigations into the motion characteristics of bubbles in liquids (Bhaga and Weber 1981, Logvinovitch 1969, Clift et al 1978, Coutanceau and Thizon 1981, Lauer et al 2012, and determined the dynamic behaviour of bubbles in different viscous liquids. Through further research, it was found that the ventilated cavity covering the surface of an underwater vehicle can effectively reduce the travelling resistance (Jiang et al 2019, Zou et al 2021, which provides a new direction of research into underwater vehicles. Kim and Kim (2015) further studied the hydrodynamic characteristics of ventilated supercavities and established a dynamic model for vehicles that produced this phenomenon.…”
Section: Introductionmentioning
confidence: 99%